2020
DOI: 10.2147/dhps.s246050
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pharmaceutical Quality of Selected Metronidazole and Ciprofloxacin Infusions Marketed in South Eastern Nigeria</p>

Abstract: Background: Pharmaceutical products need to be of good quality and it is even more critical when it comes to life saving medicaments like infusions. Objective: This research surveyed the quality fitness of some ciprofloxacin and metronidazole infusion samples marketed in Southeastern of Nigeria. Methods: Using Official Compendial methods, microbiological quality, active pharmaceutical ingredients quantitation, pH and particle count tests were evaluated on eighty infusion bottles (from eight pharmaceutical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…All the samples used in this study passed the microbiological tests similar to the results obtained on childhood immunization vaccines [16]but differs from another study on metronidazole and ciprofloxacin infusions marketed in south Eastern Nigeria [13], were it was reported that 18.75% of the infusions failed the microbiological tests. Similarly, all samples of the magnesium sulphate tested in the present study passed the content analysis test.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…All the samples used in this study passed the microbiological tests similar to the results obtained on childhood immunization vaccines [16]but differs from another study on metronidazole and ciprofloxacin infusions marketed in south Eastern Nigeria [13], were it was reported that 18.75% of the infusions failed the microbiological tests. Similarly, all samples of the magnesium sulphate tested in the present study passed the content analysis test.…”
Section: Discussionsupporting
confidence: 61%
“…This study reveals that substandard magnesium sulphate injections are in circulation in Anambra state and potentially other states in the country. Quality medicines, safe portable water and immunization are pivotal to the attainment of quality healthcare [13,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicines sold in these markets are frequently found to have ingredients at concentrations that are too high or too low. 14 For example, a drug quality study from 10 African countries found that nearly a quarter of generic antihypertensive medicines were of low quality. 15 Similarly, a study on quality assessment of seven cardiovascular drugs in 10 sub-Saharan countries indicated that 12.5% of furosemide samples were identified as being poor quality.…”
Section: Introductionmentioning
confidence: 99%
“…Poor-quality medicines present a serious public health problem, particularly in emerging economies and developing countries like Nigeria [1,2]. It poses a significant impact on the national, clinical and economic burden [3].…”
Section: Introductionmentioning
confidence: 99%